Correction: Hydrogen evolution reaction catalyzed by ruthenium ion-complexed graphitic carbon nitride nanosheets. Issue 36 (5th September 2017) - Peng, Yi; Lu, Bingzhang; Chen, Limei; Wang, Nan; Lu, Jia En; Ping, Yuan; Chen, Shaowei
Abstract : Correction for 'Hydrogen evolution reaction catalyzed by ruthenium ion-complexed graphitic carbon nitride nanosheets' by Yi Peng et al., J. Mater. Chem. A, 2017, DOI: 10.1039/c7ta03826g.